A Pilot Study of Peripheral Blood Neutrophil Aldose Reductase Expression in Pediatric Sepsis - Hugh J. Ladd; Qin , Wang; Phyllus Y. Mong; Thyyar M. Ravindranth; J. Scott Baird (Asian Journal of Clinical Pediatrics and Neonatology, 2013)
Background: The role played by Aldose Reductase (AR) in chronic diabetic complications is well documented, though its role in acute inflammation is under investigation. AR expression in rodents can be associated with an exacerbated, acute inflammatory response. However, it is not known if AR has a role in acute inflammation in children e.g. Acute Lung Injury (ALI) and/or Acute Respiratory Distress Syndrome (ARDS) associated with sepsis. Objective: Our study was carried out in order to determine whether AR protein expression in peripheral blood neutrophils of children with acute respiratory failure would be increased in those with sepsis or ALI compared to other children. Methods: Patients <18 years of age with acute respiratory failure were enrolled in an observational cohort study. We measured AR protein expression in peripheral blood neutrophils by Western blot and correlated with clinical markers for critical illness, sepsis, and lung injury. Results: Of 16 subjects (median age: 6, range: 0.7-18 years), 4 had ALI (2 with acute respiratory distress syndrome) and 7 had sepsis (3 with septic shock). AR protein expression was detected in 4 subjects, and each of these subjects had sepsis (1 with septic shock) while 1 also had ALI. Subjects with AR protein expression were similar to all other subjects with respect to PRISM III score, peak oxygenation index, lowest PaO2/FiO2, length of mechanical ventilation and oxygen therapy, duration of PICU stay, peak glucose at 24 hours and mortality. Conclusion: AR protein expression was associated with sepsis (p=0.02); not enough patients with ALI were recruited to permit analysis.